Water-Cement-Density Ratio Law for the 28-Day Compressive Strength Prediction of Cement-Based Materials - Siqi Li; Jinbo Yang; Peng Zhang (Advances in Materials Science and Engineering)
In the present contribution, the water-cement-density ratio law for the standard curing 28-day compressive strength of cement-based materials including grout, normal concrete, ceramsite concrete, and foamed concrete is proposed. The standard curing 28-day compressive strength of different grouts, normal concrete, ceramsite concrete, and foamed concrete was tested. Simulations for Abrams’ law, Bolomey’s formula, and water-cement-density ratio law were carried out and compared. The water-cement-density ratio law illustrates better simulations for the prediction of the 28-day compressive strength of cement-based materials. The water-cement-density ratio law includes both the water-cement ratio and relative apparent density of the cement-based material. Relative apparent density of the cement-based material is an important one of all the factors determining the compressive strength of the cement-based material. The water-cement-density ratio law will be beneficial for the precise and generalized prediction of the 28-day standard curing compressive strength of cement-based materials.